The Readibility of Articles in Electronic Book for Schools Indonesian Language Textbook - Imam Safi'i; Wini Tarmini; Sobri Sobri (Jurnal Pendidikan Edutama, 2021)
The purpose of this study is to describe the readability rate of articles contained in Electronic Book for Schools (EBS), Indonesian Language textbook for High School students, The author is using Flesch Formula technique in measuring the readability of the articles, which is “RE = 206,835 – (1,015  ASL) – (84,6  ASW)”, In The said analysis, we take two paragraphs from each article as a sample for the measurement of the readability, Based on our study, we know that the average readability of an article in Electronic Book for Schools (EBS), Indonesian Language textbook is very low, which is -15,79, The result of this research can be utilized as the basis in choosing articles or texts for reference materials in teaching Indonesian language for high school students,Abstrak Tujuan penelitian ini adalah untuk menggambarkan tingkat keterbacaan artikel yang terkandung dalam Buku Sekolah Elektronik (BSE), buku teks Bahasa Indonesia untuk siswa SMA, Metode yang digunakan untuk mengukur tingkat keterbacaan adalah dengan menggunakan Formula Flesch, yaitu "RE = 206,835 - (1,015 ASL) - (84,6  ASW)", Dalam analisis tingkat keterbacaan tersebut, kami mengambil dua paragraf dari setiap artikel sebagai sampel untuk pengukuran keterbacaan, Berdasarkan penelitian kami, dapat diketahui, bahwa rata-rata keterbacaan wacana yang terdapat dalam Buku Sekolah Elektronik (BSE) buku teks Bahasa Indonesia untuk siswa SMA sangat rendah, yaitu -15,79, Hasil penelitian ini dapat digunakan sebagai dasar dalam memilih artikel atau teks untuk bahan referensi dalam pengajaran bahasa Indonesia untuk siswa sekolah menengah,